Considerações sobre a epidemiologia dos primeiros casos autóctones de doença de Chagas registrados em Belém, Pará, Brasil Observations on the epidemiology of the first autochthonous cases of Chagas' disease in Belém, State of Pará, Brazil - Jeffrey Shaw; Ralph Lainson; Habid Fraiha (Universidade de São Paulo, 1969)
Quatro casos de doença de Chagas são registrados numa família em Belém, Pará, Brasil. Acredita-se que a infecção foi adquirida em Belém. Como não foram encontrados triatomíneos na casa dos doentes, nem nas residências vizinhas, sugere-se que outros meios de transmissão devem ser considerados, por exemplo a transmissão "per os". Four cases of Chagas' Disease are recorded in a single family from Belém, Pará, Brazil. The authors feel that these infections were acquired in Belém. However, the were unable to find any reduviid bugs in the house and surrounding dwelling places and suggested that other methods of transmission might be considered, for instance per os.